Transition Curves for Highway Geometric Design - Kobryń, Andrzej; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides concise descriptions of the various solutions of transition curves, which can be used in geometric design of roads and highways. It presents mathematical methods and curvature functions for defining transition curves. .
Introduction -- Simple horizontal and vertical curves -- Mathematical methods for defining of transition curves -- Transition curves described using curvature function -- Transition curves described using explicit function -- Transition curves defined in the polar coordinate system -- Polynomial description of transition curves -- Sample applications of transition curves in horizontal alignment -- Sample applications of transition curves in vertical alignment.
Keywords: Transportation engineering; Traffic engineering; Building construction; Engineering geology; Geometry; Transportation Technology and Traffic Engineering; Solid Construction; Geoengineering; Geometry